merged
authorhaftmann
Mon, 08 Feb 2010 17:13:45 +0100
changeset 35052 ca23d57b94ec
parent 35051 648e492abc43 (current diff)
parent 35040 e42e7f133d94 (diff)
child 35053 43175817d83b
merged
--- /dev/null	Thu Jan 01 00:00:00 1970 +0000
+++ b/src/HOL/Library/Lattice_Algebras.thy	Mon Feb 08 17:13:45 2010 +0100
@@ -0,0 +1,557 @@
+(* Author: Steven Obua, TU Muenchen *)
+
+header {* Various algebraic structures combined with a lattice *}
+
+theory Lattice_Algebras
+imports Complex_Main
+begin
+
+class semilattice_inf_ab_group_add = ordered_ab_group_add + semilattice_inf
+begin
+
+lemma add_inf_distrib_left:
+  "a + inf b c = inf (a + b) (a + c)"
+apply (rule antisym)
+apply (simp_all add: le_infI)
+apply (rule add_le_imp_le_left [of "uminus a"])
+apply (simp only: add_assoc [symmetric], simp)
+apply rule
+apply (rule add_le_imp_le_left[of "a"], simp only: add_assoc[symmetric], simp)+
+done
+
+lemma add_inf_distrib_right:
+  "inf a b + c = inf (a + c) (b + c)"
+proof -
+  have "c + inf a b = inf (c+a) (c+b)" by (simp add: add_inf_distrib_left)
+  thus ?thesis by (simp add: add_commute)
+qed
+
+end
+
+class semilattice_sup_ab_group_add = ordered_ab_group_add + semilattice_sup
+begin
+
+lemma add_sup_distrib_left:
+  "a + sup b c = sup (a + b) (a + c)" 
+apply (rule antisym)
+apply (rule add_le_imp_le_left [of "uminus a"])
+apply (simp only: add_assoc[symmetric], simp)
+apply rule
+apply (rule add_le_imp_le_left [of "a"], simp only: add_assoc[symmetric], simp)+
+apply (rule le_supI)
+apply (simp_all)
+done
+
+lemma add_sup_distrib_right:
+  "sup a b + c = sup (a+c) (b+c)"
+proof -
+  have "c + sup a b = sup (c+a) (c+b)" by (simp add: add_sup_distrib_left)
+  thus ?thesis by (simp add: add_commute)
+qed
+
+end
+
+class lattice_ab_group_add = ordered_ab_group_add + lattice
+begin
+
+subclass semilattice_inf_ab_group_add ..
+subclass semilattice_sup_ab_group_add ..
+
+lemmas add_sup_inf_distribs = add_inf_distrib_right add_inf_distrib_left add_sup_distrib_right add_sup_distrib_left
+
+lemma inf_eq_neg_sup: "inf a b = - sup (-a) (-b)"
+proof (rule inf_unique)
+  fix a b :: 'a
+  show "- sup (-a) (-b) \<le> a"
+    by (rule add_le_imp_le_right [of _ "sup (uminus a) (uminus b)"])
+      (simp, simp add: add_sup_distrib_left)
+next
+  fix a b :: 'a
+  show "- sup (-a) (-b) \<le> b"
+    by (rule add_le_imp_le_right [of _ "sup (uminus a) (uminus b)"])
+      (simp, simp add: add_sup_distrib_left)
+next
+  fix a b c :: 'a
+  assume "a \<le> b" "a \<le> c"
+  then show "a \<le> - sup (-b) (-c)" by (subst neg_le_iff_le [symmetric])
+    (simp add: le_supI)
+qed
+  
+lemma sup_eq_neg_inf: "sup a b = - inf (-a) (-b)"
+proof (rule sup_unique)
+  fix a b :: 'a
+  show "a \<le> - inf (-a) (-b)"
+    by (rule add_le_imp_le_right [of _ "inf (uminus a) (uminus b)"])
+      (simp, simp add: add_inf_distrib_left)
+next
+  fix a b :: 'a
+  show "b \<le> - inf (-a) (-b)"
+    by (rule add_le_imp_le_right [of _ "inf (uminus a) (uminus b)"])
+      (simp, simp add: add_inf_distrib_left)
+next
+  fix a b c :: 'a
+  assume "a \<le> c" "b \<le> c"
+  then show "- inf (-a) (-b) \<le> c" by (subst neg_le_iff_le [symmetric])
+    (simp add: le_infI)
+qed
+
+lemma neg_inf_eq_sup: "- inf a b = sup (-a) (-b)"
+by (simp add: inf_eq_neg_sup)
+
+lemma neg_sup_eq_inf: "- sup a b = inf (-a) (-b)"
+by (simp add: sup_eq_neg_inf)
+
+lemma add_eq_inf_sup: "a + b = sup a b + inf a b"
+proof -
+  have "0 = - inf 0 (a-b) + inf (a-b) 0" by (simp add: inf_commute)
+  hence "0 = sup 0 (b-a) + inf (a-b) 0" by (simp add: inf_eq_neg_sup)
+  hence "0 = (-a + sup a b) + (inf a b + (-b))"
+    by (simp add: add_sup_distrib_left add_inf_distrib_right)
+       (simp add: algebra_simps)
+  thus ?thesis by (simp add: algebra_simps)
+qed
+
+subsection {* Positive Part, Negative Part, Absolute Value *}
+
+definition
+  nprt :: "'a \<Rightarrow> 'a" where
+  "nprt x = inf x 0"
+
+definition
+  pprt :: "'a \<Rightarrow> 'a" where
+  "pprt x = sup x 0"
+
+lemma pprt_neg: "pprt (- x) = - nprt x"
+proof -
+  have "sup (- x) 0 = sup (- x) (- 0)" unfolding minus_zero ..
+  also have "\<dots> = - inf x 0" unfolding neg_inf_eq_sup ..
+  finally have "sup (- x) 0 = - inf x 0" .
+  then show ?thesis unfolding pprt_def nprt_def .
+qed
+
+lemma nprt_neg: "nprt (- x) = - pprt x"
+proof -
+  from pprt_neg have "pprt (- (- x)) = - nprt (- x)" .
+  then have "pprt x = - nprt (- x)" by simp
+  then show ?thesis by simp
+qed
+
+lemma prts: "a = pprt a + nprt a"
+by (simp add: pprt_def nprt_def add_eq_inf_sup[symmetric])
+
+lemma zero_le_pprt[simp]: "0 \<le> pprt a"
+by (simp add: pprt_def)
+
+lemma nprt_le_zero[simp]: "nprt a \<le> 0"
+by (simp add: nprt_def)
+
+lemma le_eq_neg: "a \<le> - b \<longleftrightarrow> a + b \<le> 0" (is "?l = ?r")
+proof -
+  have a: "?l \<longrightarrow> ?r"
+    apply (auto)
+    apply (rule add_le_imp_le_right[of _ "uminus b" _])
+    apply (simp add: add_assoc)
+    done
+  have b: "?r \<longrightarrow> ?l"
+    apply (auto)
+    apply (rule add_le_imp_le_right[of _ "b" _])
+    apply (simp)
+    done
+  from a b show ?thesis by blast
+qed
+
+lemma pprt_0[simp]: "pprt 0 = 0" by (simp add: pprt_def)
+lemma nprt_0[simp]: "nprt 0 = 0" by (simp add: nprt_def)
+
+lemma pprt_eq_id [simp, noatp]: "0 \<le> x \<Longrightarrow> pprt x = x"
+  by (simp add: pprt_def sup_aci sup_absorb1)
+
+lemma nprt_eq_id [simp, noatp]: "x \<le> 0 \<Longrightarrow> nprt x = x"
+  by (simp add: nprt_def inf_aci inf_absorb1)
+
+lemma pprt_eq_0 [simp, noatp]: "x \<le> 0 \<Longrightarrow> pprt x = 0"
+  by (simp add: pprt_def sup_aci sup_absorb2)
+
+lemma nprt_eq_0 [simp, noatp]: "0 \<le> x \<Longrightarrow> nprt x = 0"
+  by (simp add: nprt_def inf_aci inf_absorb2)
+
+lemma sup_0_imp_0: "sup a (- a) = 0 \<Longrightarrow> a = 0"
+proof -
+  {
+    fix a::'a
+    assume hyp: "sup a (-a) = 0"
+    hence "sup a (-a) + a = a" by (simp)
+    hence "sup (a+a) 0 = a" by (simp add: add_sup_distrib_right) 
+    hence "sup (a+a) 0 <= a" by (simp)
+    hence "0 <= a" by (blast intro: order_trans inf_sup_ord)
+  }
+  note p = this
+  assume hyp:"sup a (-a) = 0"
+  hence hyp2:"sup (-a) (-(-a)) = 0" by (simp add: sup_commute)
+  from p[OF hyp] p[OF hyp2] show "a = 0" by simp
+qed
+
+lemma inf_0_imp_0: "inf a (-a) = 0 \<Longrightarrow> a = 0"
+apply (simp add: inf_eq_neg_sup)
+apply (simp add: sup_commute)
+apply (erule sup_0_imp_0)
+done
+
+lemma inf_0_eq_0 [simp, noatp]: "inf a (- a) = 0 \<longleftrightarrow> a = 0"
+by (rule, erule inf_0_imp_0) simp
+
+lemma sup_0_eq_0 [simp, noatp]: "sup a (- a) = 0 \<longleftrightarrow> a = 0"
+by (rule, erule sup_0_imp_0) simp
+
+lemma zero_le_double_add_iff_zero_le_single_add [simp]:
+  "0 \<le> a + a \<longleftrightarrow> 0 \<le> a"
+proof
+  assume "0 <= a + a"
+  hence a:"inf (a+a) 0 = 0" by (simp add: inf_commute inf_absorb1)
+  have "(inf a 0)+(inf a 0) = inf (inf (a+a) 0) a" (is "?l=_")
+    by (simp add: add_sup_inf_distribs inf_aci)
+  hence "?l = 0 + inf a 0" by (simp add: a, simp add: inf_commute)
+  hence "inf a 0 = 0" by (simp only: add_right_cancel)
+  then show "0 <= a" unfolding le_iff_inf by (simp add: inf_commute)
+next
+  assume a: "0 <= a"
+  show "0 <= a + a" by (simp add: add_mono[OF a a, simplified])
+qed
+
+lemma double_zero [simp]:
+  "a + a = 0 \<longleftrightarrow> a = 0"
+proof
+  assume assm: "a + a = 0"
+  then have "a + a + - a = - a" by simp
+  then have "a + (a + - a) = - a" by (simp only: add_assoc)
+  then have a: "- a = a" by simp
+  show "a = 0" apply (rule antisym)
+  apply (unfold neg_le_iff_le [symmetric, of a])
+  unfolding a apply simp
+  unfolding zero_le_double_add_iff_zero_le_single_add [symmetric, of a]
+  unfolding assm unfolding le_less apply simp_all done
+next
+  assume "a = 0" then show "a + a = 0" by simp
+qed
+
+lemma zero_less_double_add_iff_zero_less_single_add [simp]:
+  "0 < a + a \<longleftrightarrow> 0 < a"
+proof (cases "a = 0")
+  case True then show ?thesis by auto
+next
+  case False then show ?thesis (*FIXME tune proof*)
+  unfolding less_le apply simp apply rule
+  apply clarify
+  apply rule
+  apply assumption
+  apply (rule notI)
+  unfolding double_zero [symmetric, of a] apply simp
+  done
+qed
+
+lemma double_add_le_zero_iff_single_add_le_zero [simp]:
+  "a + a \<le> 0 \<longleftrightarrow> a \<le> 0" 
+proof -
+  have "a + a \<le> 0 \<longleftrightarrow> 0 \<le> - (a + a)" by (subst le_minus_iff, simp)
+  moreover have "\<dots> \<longleftrightarrow> a \<le> 0" by (simp add: zero_le_double_add_iff_zero_le_single_add)
+  ultimately show ?thesis by blast
+qed
+
+lemma double_add_less_zero_iff_single_less_zero [simp]:
+  "a + a < 0 \<longleftrightarrow> a < 0"
+proof -
+  have "a + a < 0 \<longleftrightarrow> 0 < - (a + a)" by (subst less_minus_iff, simp)
+  moreover have "\<dots> \<longleftrightarrow> a < 0" by (simp add: zero_less_double_add_iff_zero_less_single_add)
+  ultimately show ?thesis by blast
+qed
+
+declare neg_inf_eq_sup [simp] neg_sup_eq_inf [simp]
+
+lemma le_minus_self_iff: "a \<le> - a \<longleftrightarrow> a \<le> 0"
+proof -
+  from add_le_cancel_left [of "uminus a" "plus a a" zero]
+  have "(a <= -a) = (a+a <= 0)" 
+    by (simp add: add_assoc[symmetric])
+  thus ?thesis by simp
+qed
+
+lemma minus_le_self_iff: "- a \<le> a \<longleftrightarrow> 0 \<le> a"
+proof -
+  from add_le_cancel_left [of "uminus a" zero "plus a a"]
+  have "(-a <= a) = (0 <= a+a)" 
+    by (simp add: add_assoc[symmetric])
+  thus ?thesis by simp
+qed
+
+lemma zero_le_iff_zero_nprt: "0 \<le> a \<longleftrightarrow> nprt a = 0"
+unfolding le_iff_inf by (simp add: nprt_def inf_commute)
+
+lemma le_zero_iff_zero_pprt: "a \<le> 0 \<longleftrightarrow> pprt a = 0"
+unfolding le_iff_sup by (simp add: pprt_def sup_commute)
+
+lemma le_zero_iff_pprt_id: "0 \<le> a \<longleftrightarrow> pprt a = a"
+unfolding le_iff_sup by (simp add: pprt_def sup_commute)
+
+lemma zero_le_iff_nprt_id: "a \<le> 0 \<longleftrightarrow> nprt a = a"
+unfolding le_iff_inf by (simp add: nprt_def inf_commute)
+
+lemma pprt_mono [simp, noatp]: "a \<le> b \<Longrightarrow> pprt a \<le> pprt b"
+unfolding le_iff_sup by (simp add: pprt_def sup_aci sup_assoc [symmetric, of a])
+
+lemma nprt_mono [simp, noatp]: "a \<le> b \<Longrightarrow> nprt a \<le> nprt b"
+unfolding le_iff_inf by (simp add: nprt_def inf_aci inf_assoc [symmetric, of a])
+
+end
+
+lemmas add_sup_inf_distribs = add_inf_distrib_right add_inf_distrib_left add_sup_distrib_right add_sup_distrib_left
+
+
+class lattice_ab_group_add_abs = lattice_ab_group_add + abs +
+  assumes abs_lattice: "\<bar>a\<bar> = sup a (- a)"
+begin
+
+lemma abs_prts: "\<bar>a\<bar> = pprt a - nprt a"
+proof -
+  have "0 \<le> \<bar>a\<bar>"
+  proof -
+    have a: "a \<le> \<bar>a\<bar>" and b: "- a \<le> \<bar>a\<bar>" by (auto simp add: abs_lattice)
+    show ?thesis by (rule add_mono [OF a b, simplified])
+  qed
+  then have "0 \<le> sup a (- a)" unfolding abs_lattice .
+  then have "sup (sup a (- a)) 0 = sup a (- a)" by (rule sup_absorb1)
+  then show ?thesis
+    by (simp add: add_sup_inf_distribs sup_aci
+      pprt_def nprt_def diff_minus abs_lattice)
+qed
+
+subclass ordered_ab_group_add_abs
+proof
+  have abs_ge_zero [simp]: "\<And>a. 0 \<le> \<bar>a\<bar>"
+  proof -
+    fix a b
+    have a: "a \<le> \<bar>a\<bar>" and b: "- a \<le> \<bar>a\<bar>" by (auto simp add: abs_lattice)
+    show "0 \<le> \<bar>a\<bar>" by (rule add_mono [OF a b, simplified])
+  qed
+  have abs_leI: "\<And>a b. a \<le> b \<Longrightarrow> - a \<le> b \<Longrightarrow> \<bar>a\<bar> \<le> b"
+    by (simp add: abs_lattice le_supI)
+  fix a b
+  show "0 \<le> \<bar>a\<bar>" by simp
+  show "a \<le> \<bar>a\<bar>"
+    by (auto simp add: abs_lattice)
+  show "\<bar>-a\<bar> = \<bar>a\<bar>"
+    by (simp add: abs_lattice sup_commute)
+  show "a \<le> b \<Longrightarrow> - a \<le> b \<Longrightarrow> \<bar>a\<bar> \<le> b" by (fact abs_leI)
+  show "\<bar>a + b\<bar> \<le> \<bar>a\<bar> + \<bar>b\<bar>"
+  proof -
+    have g:"abs a + abs b = sup (a+b) (sup (-a-b) (sup (-a+b) (a + (-b))))" (is "_=sup ?m ?n")
+      by (simp add: abs_lattice add_sup_inf_distribs sup_aci diff_minus)
+    have a:"a+b <= sup ?m ?n" by (simp)
+    have b:"-a-b <= ?n" by (simp) 
+    have c:"?n <= sup ?m ?n" by (simp)
+    from b c have d: "-a-b <= sup ?m ?n" by(rule order_trans)
+    have e:"-a-b = -(a+b)" by (simp add: diff_minus)
+    from a d e have "abs(a+b) <= sup ?m ?n" 
+      by (drule_tac abs_leI, auto)
+    with g[symmetric] show ?thesis by simp
+  qed
+qed
+
+end
+
+lemma sup_eq_if:
+  fixes a :: "'a\<Colon>{lattice_ab_group_add, linorder}"
+  shows "sup a (- a) = (if a < 0 then - a else a)"
+proof -
+  note add_le_cancel_right [of a a "- a", symmetric, simplified]
+  moreover note add_le_cancel_right [of "-a" a a, symmetric, simplified]
+  then show ?thesis by (auto simp: sup_max min_max.sup_absorb1 min_max.sup_absorb2)
+qed
+
+lemma abs_if_lattice:
+  fixes a :: "'a\<Colon>{lattice_ab_group_add_abs, linorder}"
+  shows "\<bar>a\<bar> = (if a < 0 then - a else a)"
+by auto
+
+lemma estimate_by_abs:
+  "a + b <= (c::'a::lattice_ab_group_add_abs) \<Longrightarrow> a <= c + abs b" 
+proof -
+  assume "a+b <= c"
+  hence 2: "a <= c+(-b)" by (simp add: algebra_simps)
+  have 3: "(-b) <= abs b" by (rule abs_ge_minus_self)
+  show ?thesis by (rule le_add_right_mono[OF 2 3])
+qed
+
+class lattice_ring = ordered_ring + lattice_ab_group_add_abs
+begin
+
+subclass semilattice_inf_ab_group_add ..
+subclass semilattice_sup_ab_group_add ..
+
+end
+
+lemma abs_le_mult: "abs (a * b) \<le> (abs a) * (abs (b::'a::lattice_ring))" 
+proof -
+  let ?x = "pprt a * pprt b - pprt a * nprt b - nprt a * pprt b + nprt a * nprt b"
+  let ?y = "pprt a * pprt b + pprt a * nprt b + nprt a * pprt b + nprt a * nprt b"
+  have a: "(abs a) * (abs b) = ?x"
+    by (simp only: abs_prts[of a] abs_prts[of b] algebra_simps)
+  {
+    fix u v :: 'a
+    have bh: "\<lbrakk>u = a; v = b\<rbrakk> \<Longrightarrow> 
+              u * v = pprt a * pprt b + pprt a * nprt b + 
+                      nprt a * pprt b + nprt a * nprt b"
+      apply (subst prts[of u], subst prts[of v])
+      apply (simp add: algebra_simps) 
+      done
+  }
+  note b = this[OF refl[of a] refl[of b]]
+  note addm = add_mono[of "0::'a" _ "0::'a", simplified]
+  note addm2 = add_mono[of _ "0::'a" _ "0::'a", simplified]
+  have xy: "- ?x <= ?y"
+    apply (simp)
+    apply (rule_tac y="0::'a" in order_trans)
+    apply (rule addm2)
+    apply (simp_all add: mult_nonneg_nonneg mult_nonpos_nonpos)
+    apply (rule addm)
+    apply (simp_all add: mult_nonneg_nonneg mult_nonpos_nonpos)
+    done
+  have yx: "?y <= ?x"
+    apply (simp add:diff_def)
+    apply (rule_tac y=0 in order_trans)
+    apply (rule addm2, (simp add: mult_nonneg_nonpos mult_nonneg_nonpos2)+)
+    apply (rule addm, (simp add: mult_nonneg_nonpos mult_nonneg_nonpos2)+)
+    done
+  have i1: "a*b <= abs a * abs b" by (simp only: a b yx)
+  have i2: "- (abs a * abs b) <= a*b" by (simp only: a b xy)
+  show ?thesis
+    apply (rule abs_leI)
+    apply (simp add: i1)
+    apply (simp add: i2[simplified minus_le_iff])
+    done
+qed
+
+instance lattice_ring \<subseteq> ordered_ring_abs
+proof
+  fix a b :: "'a\<Colon> lattice_ring"
+  assume "(0 \<le> a \<or> a \<le> 0) \<and> (0 \<le> b \<or> b \<le> 0)"
+  show "abs (a*b) = abs a * abs b"
+  proof -
+    have s: "(0 <= a*b) | (a*b <= 0)"
+      apply (auto)    
+      apply (rule_tac split_mult_pos_le)
+      apply (rule_tac contrapos_np[of "a*b <= 0"])
+      apply (simp)
+      apply (rule_tac split_mult_neg_le)
+      apply (insert prems)
+      apply (blast)
+      done
+    have mulprts: "a * b = (pprt a + nprt a) * (pprt b + nprt b)"
+      by (simp add: prts[symmetric])
+    show ?thesis
+    proof cases
+      assume "0 <= a * b"
+      then show ?thesis
+        apply (simp_all add: mulprts abs_prts)
+        apply (insert prems)
+        apply (auto simp add: 
+          algebra_simps 
+          iffD1[OF zero_le_iff_zero_nprt] iffD1[OF le_zero_iff_zero_pprt]
+          iffD1[OF le_zero_iff_pprt_id] iffD1[OF zero_le_iff_nprt_id])
+          apply(drule (1) mult_nonneg_nonpos[of a b], simp)
+          apply(drule (1) mult_nonneg_nonpos2[of b a], simp)
+        done
+    next
+      assume "~(0 <= a*b)"
+      with s have "a*b <= 0" by simp
+      then show ?thesis
+        apply (simp_all add: mulprts abs_prts)
+        apply (insert prems)
+        apply (auto simp add: algebra_simps)
+        apply(drule (1) mult_nonneg_nonneg[of a b],simp)
+        apply(drule (1) mult_nonpos_nonpos[of a b],simp)
+        done
+    qed
+  qed
+qed
+
+lemma mult_le_prts:
+  assumes
+  "a1 <= (a::'a::lattice_ring)"
+  "a <= a2"
+  "b1 <= b"
+  "b <= b2"
+  shows
+  "a * b <= pprt a2 * pprt b2 + pprt a1 * nprt b2 + nprt a2 * pprt b1 + nprt a1 * nprt b1"
+proof - 
+  have "a * b = (pprt a + nprt a) * (pprt b + nprt b)" 
+    apply (subst prts[symmetric])+
+    apply simp
+    done
+  then have "a * b = pprt a * pprt b + pprt a * nprt b + nprt a * pprt b + nprt a * nprt b"
+    by (simp add: algebra_simps)
+  moreover have "pprt a * pprt b <= pprt a2 * pprt b2"
+    by (simp_all add: prems mult_mono)
+  moreover have "pprt a * nprt b <= pprt a1 * nprt b2"
+  proof -
+    have "pprt a * nprt b <= pprt a * nprt b2"
+      by (simp add: mult_left_mono prems)
+    moreover have "pprt a * nprt b2 <= pprt a1 * nprt b2"
+      by (simp add: mult_right_mono_neg prems)
+    ultimately show ?thesis
+      by simp
+  qed
+  moreover have "nprt a * pprt b <= nprt a2 * pprt b1"
+  proof - 
+    have "nprt a * pprt b <= nprt a2 * pprt b"
+      by (simp add: mult_right_mono prems)
+    moreover have "nprt a2 * pprt b <= nprt a2 * pprt b1"
+      by (simp add: mult_left_mono_neg prems)
+    ultimately show ?thesis
+      by simp
+  qed
+  moreover have "nprt a * nprt b <= nprt a1 * nprt b1"
+  proof -
+    have "nprt a * nprt b <= nprt a * nprt b1"
+      by (simp add: mult_left_mono_neg prems)
+    moreover have "nprt a * nprt b1 <= nprt a1 * nprt b1"
+      by (simp add: mult_right_mono_neg prems)
+    ultimately show ?thesis
+      by simp
+  qed
+  ultimately show ?thesis
+    by - (rule add_mono | simp)+
+qed
+
+lemma mult_ge_prts:
+  assumes
+  "a1 <= (a::'a::lattice_ring)"
+  "a <= a2"
+  "b1 <= b"
+  "b <= b2"
+  shows
+  "a * b >= nprt a1 * pprt b2 + nprt a2 * nprt b2 + pprt a1 * pprt b1 + pprt a2 * nprt b1"
+proof - 
+  from prems have a1:"- a2 <= -a" by auto
+  from prems have a2: "-a <= -a1" by auto
+  from mult_le_prts[of "-a2" "-a" "-a1" "b1" b "b2", OF a1 a2 prems(3) prems(4), simplified nprt_neg pprt_neg] 
+  have le: "- (a * b) <= - nprt a1 * pprt b2 + - nprt a2 * nprt b2 + - pprt a1 * pprt b1 + - pprt a2 * nprt b1" by simp  
+  then have "-(- nprt a1 * pprt b2 + - nprt a2 * nprt b2 + - pprt a1 * pprt b1 + - pprt a2 * nprt b1) <= a * b"
+    by (simp only: minus_le_iff)
+  then show ?thesis by simp
+qed
+
+instance int :: lattice_ring
+proof  
+  fix k :: int
+  show "abs k = sup k (- k)"
+    by (auto simp add: sup_int_def)
+qed
+
+instance real :: lattice_ring
+proof
+  fix a :: real
+  show "abs a = sup a (- a)"
+    by (auto simp add: sup_real_def)
+qed
+
+end